Progressive Covenantalism sebagai Jembatan Hermeneutis: Rekonsiliasi Dispensasionalisme dan Teologi Perjanjian dalam Penafsiran 1 Petrus 29 - Supriyanto Freddy (Student Evangelical Journal Aiming At Theological Interpretation, 2025)
This study examines Progressive Covenantalism as an alternative hermeneutical framework for understanding the relationship between Israel and the Church, with a focus on 1 Peter 2:9. In response to the sharp contrast between Dispensationalism and Covenant Theology, this paradigm views the Church as the progressive fulfillment of God's promises in Christ, while still acknowledging Israel’s distinctive role. A qualitative approach is employed through analysis of the Greek text, intertextual study with the Old Testament, and comparative evaluation of key theological literature from the three paradigms. The findings indicate that Progressive Covenantalism more effectively maintains redemptive-historical continuity without negating Israel’s vocation. This approach offers significant implications for the development of ecclesiology and theological discourse in Indonesia. The main contribution lies in introducing Progressive Covenantalism to the Indonesian theological context and offering a balanced interpretive model for 1 Peter 2:9. Keywords: Progressive Covenantalism, 1 Peter 2:9, Israel and the Church, Hermeneutics